Muscle activity of the latissimus dorsi after tendon transfer in patients with rotator cuff tears - Hetto, Pit; Spranz, David Maximilian; Zeifang, Felix; Wolf, Sebastian Immanuel; van Drongelen, Stefan; Maier, Michael Wolfgang; Sowa, Boris (Journal of Clinical Medicine, 2020)
Background: Massive irreparable posterosuperior rotator cuff tears may result in the loss of external rotation. Most of the patients with posterosuperior rotator cuff tears suffer from a restriction in their daily life actions. Latissimus dorsi tendon transfer (LDTT) is a method to restore abduction and external rotation in these patients. However, the behavior of the LD after the transfer is not clear yet. Few studies have analyzed the activity of the LD after transfer. The goal of this study was to examine the function of the LD postoperatively in follow-up examinations during activities of daily life (ADLs) and during different movements evaluated by measuring the range of motion (ROM). Methods: We examined 12 patients 4.3 years (1 - 9 years) after LDTT, using simultaneous 3D motion analysis and surface Electromyography (sEMG) of 12 muscle parts; the opposite, nonaffected side was assessed as a control. The measurement protocol included two standardized movements (exorotation with an adducted arm and exorotation with 90° abduction) as well as two ADLs (combing hair and perineal care). Results: An average of 4.3 years (1 - 9 years) after LDTT, 9 of the 12 subjects showed EMG activity in the transferred LD during glenohumeral external rotation. During the endorotation phase, either little activity was registered or only the pectoralis major was active. During the ADLs, 6 out of 12 subjects showed EMG activity in the transferred LD while “combing hair”, whereas all subjects showed EMG activity during perineal care. Conclusion: The LD showed partial activity in its new role as an exorotator, but no clear difference was observed between some of the movements as well as in comparison with the healthy shoulder. Further studies will need to be conducted to better differentiate voluntary contractions and co-contractions as well as tension and extension in the muscle.
Gesehen am 31.03.2020